Self-Reported Fatigue Predicts Incident Stroke in a General Population: EPIC-Norfolk Prospective Population-Based Study. Issue 4 (April 2020) - Barlas, Genevieve; Luben, Robert L.; Neal, Samuel R.; Wareham, Nicholas J.; Khaw, Kay-Tee; Myint, Phyo K.
Abstract : Background and Purpose—: Fatigue is a common symptom among stroke survivors and in general practice. However, the clinical significance of fatigue and its relationship to incident stroke is unclear. The aim of this study was to examine the relationship between self-reported fatigue and the incidence of stroke in a general population. Methods—: This was a prospective, population-based study. The study population was 15 654 men and women aged 39 to 79 years recruited in 1993 to 1997 and followed till March 2016. Fatigue was assessed at 18 months after baseline using the vitality domain of the Short Form 36 questionnaire. Cox proportional hazard models were constructed to describe the prospective relationship between baseline fatigue and incident stroke adjusting for age, sex, systolic blood pressure, cholesterol, physical activity, smoking status, alcohol consumption, fruit and vegetable consumption, diabetes mellitus, body mass index, vitamin supplement use, education level, Townsend deprivation index, and occupational social class. Incident stroke was ascertained using death certificates and hospital record linkage data. Results—: Through 249 248 person-years of follow-up, 1509 incident strokes occurred. Participants who reported the highest level of fatigue (quartile 4) were more likely to be women, to be multimorbid, and to perceive their health as fair or poor. We observed ≈50% relative risk increase in stroke risk (hazard ratio, 1.49 [95% CI, 1.29–1.71]) in those who reported the highest level of fatigue compared with those who reported the lowest level of fatigue (Q4 versus Q1). This relationship remained unaltered regardless of anemia status, the presence or absence of chronic bronchitis, thyroid dysfunction, or depression. Conclusions—: Self-report fatigue assessed by the vitality domain of the Short Form 36 questionnaire predicts the risk of future stroke at the general population level. Identifying and addressing stroke risk factors in those who report fatigue in general practice may have substantial benefit at the population level. Abstract : Supplemental Digital Content is available in the text.